Analysis and design of half bridge DC/DC series parallel loaded resonant converter for undergraduate teaching laboratory (UTL): article / Wan Adli Muzani Wan Mohamed - Wan Mohamed, Wan Adli Muzani (2012)
This paper proposed to design the DC power supply using half bridge LCC series parallel loaded resonant converter (HBSPRC) application for undergraduate teaching laboratory. The DC power supply input voltage is 20 - 12V and DC output voltage is maintained at 10V. The converter is design based on output power 2.0W and the starting switching frequency, fs is 50 kHz. The operation above resonance is preferred, because the power switches turn on at zero current and zero voltage. The experiment result should be compared between theoretical and computer simulation based on the application and desired output power. The operating theory and equation are also developed. Theoretical, simulations and experiments are come out to complete the analysis and design of study.